2008
DOI: 10.1111/j.1399-3038.2007.00688.x
|View full text |Cite
|
Sign up to set email alerts
|

History of respiratory infections in the first 12 yr among children from a birth cohort

Abstract: Respiratory infections are the most frequent health problem in childhood. There is little precise information on how many respiratory illness episodes can be expected in a normal child. This study was designed to create reference values for the frequency of respiratory infections as recordable by history. Respiratory illnesses were recorded in a prospective birth cohort of 1314 German children born in 1990 and tracked until age 12 yr (760 children). Parents recorded the child's illnesses in a diary and answere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
125
1
8

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(145 citation statements)
references
References 17 publications
11
125
1
8
Order By: Relevance
“…28 Our current results also support indirectly those of Grüber et al, 19 who found that having a dog at home during the first 2 years of life decreased the number of common cold episodes among 0-to 2-yearolds. We showed that children who had dog contacts at home had less otitis and rhinitis and more healthy weeks than children without dog contacts at home, but having a dog at home during the first postnatal year had no significant role in the occurrence of wheezing and cough, which is in line with earlier results, 29 even though the reason for these findings is obscure.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…28 Our current results also support indirectly those of Grüber et al, 19 who found that having a dog at home during the first 2 years of life decreased the number of common cold episodes among 0-to 2-yearolds. We showed that children who had dog contacts at home had less otitis and rhinitis and more healthy weeks than children without dog contacts at home, but having a dog at home during the first postnatal year had no significant role in the occurrence of wheezing and cough, which is in line with earlier results, 29 even though the reason for these findings is obscure.…”
Section: Discussionsupporting
confidence: 90%
“…Earlier reports on the role of animal contacts on the prevalence of respiratory tract infections are sparse. Some previous studies have shown that dog contacts, 19,20 although not cat contacts, 15 seem to decrease the number of common cold episodes during childhood. However, pet ownership has also been considered a possible risk factor for frequent childhood respiratory tract infections in some reports.…”
mentioning
confidence: 99%
“…Children can typically have up to 11 upper respiratory tract infection episodes per year in infancy, eight episodes at preschool age and four at school age (26), and 0.2-2% of these develop into clinically important bacterial sinus infection (27). A chronic mucopurulent discharge suggests a rhinosinusitis of infective origin (28) (C).…”
Section: Classic Symptoms and Signsmentioning
confidence: 99%
“…C hildren experience 4 to 12 acute respiratory infections annually, 1 and primary care clinicians too often prescribe antibiotics [2][3][4] despite strong evidence that they typically provide only marginal benefits. [5][6][7][8] Common harms and the contribution to antibiotic resistance, 9 now a global public health crisis, 10,11 are rarely addressed.…”
Section: Introductionmentioning
confidence: 99%